DEVELOPMENT OF INTERACTIVE LEARNING MEDIA ABOUT THE EARTH AND ITS SATELLITES THROUGH THE GENIALLY PLATFORM TO IMPROVE STUDENTS’ COGNITIVE LEARNING RESULTS - Aryanti Yuniarsih; Agung Mulyo Setiawan (Universitas Negeri Surabaya in collaboration with Perkumpulan Pendidik IPA Indonesia (PPII), 2025)
Science learning contains several subjects, one of which is the material of the earth and its satellites. Some students find this material difficult to understand because the material is abstract, which will affect their low cognitive learning outcomes. The purpose this research to produce an interactive learning media which is valid, feasible, effective in improving student cognitive learning outcomes on the material of the earth and its satellites through the genially platform. This research and development with 4D development stages of Thiagarajan. The results media, material, and question validation tests obtained an average 88.75%, 89.75%, 89.5% so very valid. The results teacher and student readability test obtained average 95% and 88.33% so very feasible. The results of effectiveness test using the t test obtained a significance value of 0.000 so that significant difference between pretest average and posttest average, the results N-gain analysis obtained a score of 0.56 so learning media effective improving the learning outcomes of students with a moderate category. The results student response obtained average 91.42% so very good response. Based on validation, readability, effectiveness, the interactive learning media is declared valid, feasible, effective improving student cognitive learning outcomes.